ANALISIS KEPUTUSAN KONSUMEN DALAM MELAKUKAN RESERVASI HOTEL SECARA ONLINE - Hendra Handes Sariyanto; Lelly Christin (Universitas Bunda Mulia, 2017)
Hotels improved their services such as online reservation. Therefore, these study objectives are to identify the factors that encourage consumers decision to make an online reservation, and which is the most dominant factor in influencing the consumer’s decision to make reservations online. This study used 300 respondents. From the results of interviews with 150 respondents, found five factors that encourage consumers make an online reservation. And the results of questionnaires to 150 respondents known that the dominant factor is the factor of Easy and Practice, which is efficient in time. Key Words- Reservation, Online, Hotel